“Does It Improve the Mind’s Eye?”: Sensorimotor Simulation in Episodic Event Construction - Purkart, Rudy; Versace, Rémy; Vallet, Guillaume T. (Frontiers in Psychology, 2019)
Memories are not frozen in the past. Instead, they can be dynamically combined to allow individuals to adapt to the present or even imagine the future. This recombination, called event construction, also means that it might be possible to improve memory through specific interventions such as episodic specificity induction (ESI). ESI provides brief training in recollecting the details of a past event that boosts the retrieval of specific details in subsequent tasks if these tasks involve the recombination of memories. However, very little is known about how event construction is accomplished, and this is essential if we are (1) to understand how episodic memory might work and (2) to promote a specific mechanism that will help people remember the past better. The present study assesses the sensorimotor simulation hypothesis, which has been proposed within the embodied approaches to cognition. According to these approaches, access to and the recombination of memories occur through the simulation of the sensory and motor propreties of our past experiences. This hypothesis was tested using a sensory interference paradigm. In a first phase, the participants watched videos and then received a specificity or a control induction. In a second phase, they described their memories of the videos while simultaneously viewing an interfering stimulus (dynamic visual noise; DVN) or a gray control screen. In line with a sensorimotor simulation account, the presentation of a DVN during the description of the videos led to a decrease in the number of internal details (details specific to the event) only after the specificity induction rather than the control induction. The findings provide evidence that the specificity induction targets and facilitates the sensorimotor simulation mechanism, thus confirming the crucial involvement of a mechanism of this sort in the constructive functioning of memory.